Penampilan Dan Keragaman Genetik Sifat-Sifat Kuantitatif Beberapa Aksesi Lokal Kacang Tanah (Arachis hypogaea L.) - Siwalette, Herce; Jambormias, Edizon; Laisina, Jane J K (Universitas Pattimura, 2024)
Peanut is one of the high-value food crops due to its high protein content. This research aims to test the production potential and describe the genetic diversity and heritability among accessions and within accessions of local peanuts from Tanimbar Islands and South Buru. The study was conducted from May to August 2022 at the Pattimura Pearl Garden in Ambon, using a randomized complete block design with three replications. The factor tested was accessions of six levels, each with three accessions of local peanuts from the Tanimbar Islands and two from South Buru, with the Tasia 2 variety as a reference. The results showed that the performance of the Tanimbar White accession was better than the Tasia 2 variety and other local peanut accessions. Tanimbar White had a smaller stature, with a plant height of 73 cm and earlier maturity at 85 days, superior to Tasia 2, with a plant height of 84 cm and maturity at 90 days. The seed weight of the Tanimbar White accession reached 32 g with 65 seeds per plant, relatively better than Tasia 2 with a seed weight of 28 g and 60 seeds per plant. The research also indicated genetic diversity with high heritability among accessions for all quantitative traits (0.53-1.00). However, genetic diversity still exists within families with high heritability within accessions ranging from 0.54-0.58 for traits such as pod weight (wet and dry, in grams), number of seeds, and seed weight (dry, in grams). Therefore, purification and selection of local varieties are necessary to obtain even better local varieties compared to superior varieties. These accessions have similar maturity periods and earlier maturity compared to Tasia 2, with smaller stature.